2011
DOI: 10.1002/ibd.21465
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenecity of hepatitis A vaccine in pediatric patients with inflammatory bowel disease

Abstract: HAV is both immunogenic and safe in pediatric patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…1 Their results were consistent with existing reports of HAV seroconversion in healthy patients 2 and in patients with chronic liver disease. 3,4 Of note, none of the patients in the study were on a biologic medication, such as infliximab.…”
Section: To the Editorsupporting
confidence: 91%
See 1 more Smart Citation
“…1 Their results were consistent with existing reports of HAV seroconversion in healthy patients 2 and in patients with chronic liver disease. 3,4 Of note, none of the patients in the study were on a biologic medication, such as infliximab.…”
Section: To the Editorsupporting
confidence: 91%
“…We read with great interest the recent article by Radzikowski et al 1 on immunogenicity of the hepatitis A virus (HAV) vaccine in pediatric patients with inflammatory bowel disease (IBD). As outlined by the authors, there are few studies investigating the immune response to vaccinations in children with IBD.…”
Section: To the Editormentioning
confidence: 97%
“…Modified dosing regimens, including doubling the standard antigen dose, might increase response rates in immunocompromised patients [75]. Conversely, in a pediatric IBD study of hepatitis A vaccine, the rate of seroconversion after the second dose was 97 %, which did not differ from the rate of 100 % in healthy children [76]. Moreover, several studies have concluded that the influenza vaccine is safe and effective in both children and adults with various chronic diseases [77][78][79][80][81][82][83][84][85].…”
Section: Vaccinationsmentioning
confidence: 82%
“…In two studies assessing the immune response to the hepatitis A vaccine, 97-100% of children with IBD achieved seroprotection [25,26]. There was no significant difference in the rate of seroconversion between IBD patients and healthy controls.…”
Section: Vaccine Immunogenicity In Children With Ibdmentioning
confidence: 90%
“…It is important to emphasise that the examined vaccines appeared to be safe in all of the above studies [20][21][22][23][24][25][26][27][28][29]. The most common adverse effects were reactions at the local injection site that manifested as erythema, induration, or tenderness [21][22][23][24][25][26]29].…”
Section: Vaccine Safetymentioning
confidence: 99%